Obstacle Avoider Robot - Kamis, Zulfikar Firdaus; Mohamad Yunus, Muhammad Afiezul (2016)
This final year project which is the “Obstacle Avoider Robot” refers to the problem that finding the path without an obstacle. The objective of this research is to improve the performance of the robot for smooth navigation. Then, to study the operation and relationship between PIC, sensor and the motor to create a smooth navigation. The final year project studies enhances the academic material studied at University by allowing students to apply what they have learned and to develop key professional attribute. Final year project should provide an opportunity for student such as experience on applying engineering methods such as design and problem solving and develop technical abilities.